2011
DOI: 10.1038/nature09816
|View full text |Cite
|
Sign up to set email alerts
|

Linear ubiquitination prevents inflammation and regulates immune signalling

Abstract: Members of the tumour necrosis factor (TNF) receptor superfamily have important functions in immunity and inflammation. Recently linear ubiquitin chains assembled by a complex containing HOIL-1 and HOIP (also known as RBCK1 and RNF31, respectively) were implicated in TNF signalling, yet their relevance in vivo remained uncertain. Here we identify SHARPIN as a third component of the linear ubiquitin chain assembly complex, recruited to the CD40 and TNF receptor signalling complexes together with its other const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

60
1,192
7
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 840 publications
(1,284 citation statements)
references
References 36 publications
60
1,192
7
3
Order By: Relevance
“…Upon TNFa stimulation, adaptor molecules including TNFa receptor type-1-associated death domain protein (TRADD), TNFa receptorassociated factor 2 and 5 (TRAF2 and TRAF5), cellular inhibitor of apoptosis 1 and 2 (cIAP1/2) and RIPK1 are recruited to the receptor complex (TNF receptor 1 (TNFR1) Complex I) (Figure 1), in which RIPK1 acquires a K63-linked or linear polyubiquitin chain by E3 ligases, TRAF2/5 cIAP1/2 or linear ubiquitin chain assembly complex containing two E3 ligases HOIL-1 and HOIP. [18][19][20][21][22] TAK1 is recruited and activated through TAK1-binding protein 2 (TAB2) binding to the RIPK1 polyubiquitin chain. 23,24 Upon binding the polyubiquitin chain, TAK1 phosphorylates and activates the IKK complex composed of IKKa, IKKb and NEMO (also called IKKg), which leads to phosphorylation and degradation of IkB resulting in activation of NF-kB ( Figure 1).…”
Section: Tak1 Activation and Downstream Pathwaysmentioning
confidence: 99%
“…Upon TNFa stimulation, adaptor molecules including TNFa receptor type-1-associated death domain protein (TRADD), TNFa receptorassociated factor 2 and 5 (TRAF2 and TRAF5), cellular inhibitor of apoptosis 1 and 2 (cIAP1/2) and RIPK1 are recruited to the receptor complex (TNF receptor 1 (TNFR1) Complex I) (Figure 1), in which RIPK1 acquires a K63-linked or linear polyubiquitin chain by E3 ligases, TRAF2/5 cIAP1/2 or linear ubiquitin chain assembly complex containing two E3 ligases HOIL-1 and HOIP. [18][19][20][21][22] TAK1 is recruited and activated through TAK1-binding protein 2 (TAB2) binding to the RIPK1 polyubiquitin chain. 23,24 Upon binding the polyubiquitin chain, TAK1 phosphorylates and activates the IKK complex composed of IKKa, IKKb and NEMO (also called IKKg), which leads to phosphorylation and degradation of IkB resulting in activation of NF-kB ( Figure 1).…”
Section: Tak1 Activation and Downstream Pathwaysmentioning
confidence: 99%
“…3,4 The formation of this complex is initiated by the interaction of ligand-bound TNFR1 with TNF receptor-associated death domain (TRADD) and by the recruitment of the kinase receptor interacting protein kinase 1 (RIP1), the adaptor proteins TNF receptor-associated factor 2/5 and the ubiquitin ligase cellular inhibitor of apoptosis 1/2 (c-IAP1/2) and linear ubiquitin chain assembly complex (LUBAC). [5][6][7][8][9] c-IAP1/2 and LUBAC target RIP1 for K11, K63 and linear polyubiquitination priming RIP1 for the recruitment of two kinase-containing complexes, namely, TAK1/TAK1-binding protein 1 (TAB1)/TAB2 and NEMO/ inhibitor of NF-κB kinase α (IKKα)/IKKβ. 5,[10][11][12][13] Ultimately, activation of IKKβ leads to the phosphorylation and proteasomal degradation of IκBα and the nuclear translocation of NF-κB, a pathway defined as the classical, or the canonical, NF-κB pathway.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] c-IAP1/2 and LUBAC target RIP1 for K11, K63 and linear polyubiquitination priming RIP1 for the recruitment of two kinase-containing complexes, namely, TAK1/TAK1-binding protein 1 (TAB1)/TAB2 and NEMO/ inhibitor of NF-κB kinase α (IKKα)/IKKβ. 5,[10][11][12][13] Ultimately, activation of IKKβ leads to the phosphorylation and proteasomal degradation of IκBα and the nuclear translocation of NF-κB, a pathway defined as the classical, or the canonical, NF-κB pathway. [14][15][16] Besides its role in the activation of NF-κB, the dissociation of complex I from TNFR1 triggers the recruitment of Fas-associated protein with death domain (FADD) and caspase-8 to form a cytosolic death complex, initially defined as complex II.…”
mentioning
confidence: 99%
“…The removal of Lys63‐ubiquitylation chains from adaptor protein receptor‐interacting protein 1 (RIP1) by CYLD negatively regulates NF‐κB signalling, and this deubiquitinating event blocks the aberrant expression of survival genes in germ cells 53. A mass spectrometric study showed that TNFR1 complex can conjugate with Ub system by multiple polyubiquitin linkages including K48, K63, K11 and linear chains 54. Each linkage exhibits different responses.…”
Section: K63‐ubiquitination Plays An Important Role In Nf‐κb Activatimentioning
confidence: 99%